In vitro-Studien zum genotoxischen Potential und zum Metabolismus von Mykotoxinen mit Resorcylsäurelakton- und Perylenchinon-Struktur - Fleck, Stefanie Christina (KIT Scientific Publishing, 2013)
The contamination of food and feed with mycotoxins represents a worldwide problem. In order to conduct a risk assessment, further studies on the level of contamination and the toxicity of the mycotoxins are needed. The objective of the present work was to investigate the genotoxicity and the in vitro metabolism of zearalenone as well as of Alternaria toxins with a perylene quinone structure. New insights for the risk assessment of these mycotoxins were obtained.